Examine the Outcomes of Close Mitral Commissurotomy and Compare the Findings with Balloon Mitral Volvotomy in Patients with Mitral Stenosis (Medical Forum Monthly, 2024)
Objective: To examine the results of closed mitral valvotomy with balloon mitral commissurotomy in patients with rheumatic non calcific mitral stenosis.Study Design: Comparative/observational study.Place and Duration of Study: This study was conducted at the Department of Cardiology, Mayo Hospital, Lahore from January 2018 to June 2018.Materials and Methods: Eighty two patients of both genders with ages 10 to 60 years were enrolled. Patients were categorized into two groups, Group A included 41 patients and treated with closed mitral valvotomy, Group B included 41 patients and treated with balloon mitral commissurotomy. Functional outcomes were examined of both techniques and compared the results. Follow-up was taken at 1 week and at six months after surgical treatment and results were compared.Results: There were 14 (34.15%) patients were males and 27 (65.85%) were females in group A while in Group B, 20 (48.78%) patients were males and 51.22% were females. Residual atrial septal defect was found in 4 patients at 6 months after balloon mitral commissurotomy. Severe mitral regurgitation was found in 2 patients of closed mitral valvotomy while 6 patients had severe MR of balloon mitral commissurotomy. Urgent mitral valve replacement was performed in 3 patients of balloon mitral commissurotomy. There were 1 mortality found in Group A while 2 in Group B.Conclusion: Closed mitral valvotomy resulted better outcome as compared to balloon mitral commissurotomy. Closed mitral valvotomy technique had low procedural cost as compared to balloon mital commissurotomy.